SYNTHESIS AND STRUCTURED N-ACYL AND THIOUREA DERIVATIVES CITIZINE AND ANABAZINE - O.A. Nurkenov; Nurmaganbetov Zh.S.; Seilkhanov T.M; Fazylov S.D.; Manasheva V.M; Zhasymbekova A.R.; A.S. Serikbolov (Academic Scientific Journal of Chemistry, 2020)
This work presents the results of studies on the chemical transformation of the alkaloids molecules cytisine and anabazine to obtain their N-cinnamoyl derivatives, as well as possible ways for their further modification. The optimal conditions for the preparation of N-cinnamoylcytisine and N-cinnamoylanabazine in the acylation reactions of alkaloids with cinnamoyl chloride are considered. Hydrazinolysis of the resulting Ncinnamoylcytisine and N-cinnamoylanabazine was carried out. It was shown that the interaction of acrylamide derivatives of alkaloids with hydrazine hydrate in ethanol leads to the formation of the corresponding pyrazole derivatives resulting from the intramolecular cyclocondensation of hydrazones of N-cinnamoyl derivatives. By the interaction of cinnamoylisothiocyanate with the above alkaloids, new thiourea derivatives are synthesized. The structures of the synthesized compounds were studied by 1 H and 13C NMR spectroscopy, as well as by the data of two-dimensional spectra of COSY (1 H-1 H) and HMQC (1 H-13C). The values of chemical shifts, multiplicity, and integrated intensity of 1 H and 13C signals in one-dimensional NMR spectra were determined. Using spectra in the formats COSY (1 Н1 Н) and HMQC (1 Н13С), homo- and heteronuclear interactions were established, confirming the structure of the studied compounds